Thoracic SMARCA4-deficient undifferentiated tumour: a case report - ZHANG Lanlan, YANG Qiao, NIE Zunzhen, GUO Ying (Zhenduanxue lilun yu shijian, 2023)
Thoracic SMARCA4-deficient undifferentiated tumor is a rare type of undifferentiated tumor occurring in the pleura. Their morphological features are poorly differentiated. A malignant tumor that lacks glandular, squamous, or other distinct cell lineages, as demonstrated by histological and immunohistochemical staining, is characterized by plasmacytoid and rhabdomytoid cell morphology and loss of SMARCA4 expression. We report a case of an undifferentiated tumor in the pleura with a SMARCA4 deletion,The tumor cells were plasmacytoid or rhabdomytoid，Poor cell differentiation, Immunohistochemical staining showed Syn positive in tumor cells,SMARCA4 expression is deficient,The proliferation index of Ki-67 was 80%,Other markers were all negative The patient was a heavy smoker and previously healthy.Patients with insidious onset,It was found in an advanced stage.After the surgery, no treatment was administered, and the patient survived for only 66 days.There was no significant difference in the survival time of advanced patients who received traditional treatment after surgery compared with those reported in the literature.The clinical data, histological characteristics and immunohistochemistry were retrospectively analyzed, and a review of the relevant literature suggests that SMARCA4-deficient undifferentiated tumors are highly aggressive and have a poor prognosis.